Pengaruh Kompensasi Dan Kepemimpinan Terhadap Motivasi Kerja Dan Kaitannya Dengan Kinerja - Tri diana (Jurnal Ekonomi Integra, 2016)
The method used is explanatory research and associative. Study population so that the same number of samples, a total of 107 respondents. Measurement data using a Likert scale, the data is processed by using multiple linear regression analysis. Based on the research results, simultaneously (Test F) accept the hypothesis of the influence of variable compensation and leadership simultaneously towards employee motivation. Determinansi amounted for 34.0% (R2) can be explained by the model, with the remaining 66% are influenced by other factors outside the research model. Dominance partially on work motivation in a row is a variable compensation and a variable leadership. Furthermore, the effect of motivation on the performance of significant influence by determinansi by 10.8%